An Experimental Study of Concussion Blasting for Structural Steel - Jang, Hyong Doo; Yang, H.; Ko, Y.; Kim, S.; Moon, H. (Korean Society of Explosives & Blasting Engineering, 2011)
Concussion shots were conducted for SS400, a general structural steel, and SM490, a structural steel for welding, using TNT, which is used as a standard explosive. The ability to cut the steels was compared for different combinations of charges and materials. The results show that the amount of explosives used for SM490 requires more 30% than SS400.